Os desafios do desenvolvimento territorial rural: limites e possibilidades das estratégias dos governos FHC e Lula - Mendonça, Nilton César (2005)
This work analyzes the conceptions of the rural territorial development of both Fernando Henrique Cardoso’s (FHC) and Luiz Inácio Lula da Silva’s (Lula) government so that at the end it is checked if the present government’s strategies represent some continuity in relation to the previous government. What mostly motivates for this work is the evaluation of the capability of the territorial approach to contribute in facing poverty, and social and regional differences, representing an ‘actual alternative’ of creating citizenship and competitive insertion of the dejected areas in the most dynamic regional, national e International economical circuits. The international experiences have proved the viability of these strategies of territorial development in certain conditions. They have also proved that the strategies of territorial development are not necessarily linked to the liberalizing policies. In Brazil, however, this process still encounters many difficulties to be operated as a possible and sustained alternative for creating jobs and income in the dejected regions of the country. At the end of the 1990-decade, the FHC government put in the strategies of territorial development in its programs for the rural dejected areas of the country. The current government has also implemented programs with this objective. When comparing the strategies of rural territorial development ofboth governments, this work aims at contributing with a deeper discussion of the topic, trying to identify continuities or ruptures from one to the other government.